Unveiling Namibia's Digital Humour: A Humorous and Stylistic Examination of Memes in Namibian Online Discourse (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
This article explored the humorous and stylistic elements of memes in Namibian online discourse. In the digital age, memes have become an integral part of online communication, offering valuable insights into contemporary language use. Today, memes are widely recognised as short videos or images accompanied by humorous texts, rapidly shared on social media. The incongruity theory of humour helps elucidate the humorous and language elements within memes. The study aimed at analysing selected memes within the Namibian socio-cultural context, shedding light on how language is used to create humorous effects and identifying stylistic qualities. The study employed a desktop methodology, analysing image macros from the Namibian socio-cultural context. 8 memes were sampled from an online platform called Namibian memes01 populated by 139 thousand followers at the time of sampling these memes.  The study revealed that memes serve as a form of communication, conveying emotions, thoughts, ideas, and reflecting cultural values. They contribute to language development and have the potential to shape social interactions and shared beliefs. Humour plays a significant role in memes, fostering a sense of community, defusing tension, and promoting positive interactions. The findings highlight the importance of pragmatics and context in interpreting the intended meanings of memes.
Keywords: memes; internet memes; humour; stylistic; analysis; linguistics